(untitled) (The International Journal of Educational Sciences and Arts, 2024)
The current research aims to identify the level of psychological boredom among students at the University of Mosul, and to identify the significance of the significant differences in the level of psychological boredom according to the gender variable (male - female), the specialization variable (scientific - humanities), and the academic grade variable (second – fourth). The primary research sample consisted of (802) male and female students who were selected randomly from the colleges of the University of Mosul for the academic year (2023 – 2024(. To achieve the objectives of the research, the researcher prepared a psychological boredom scale, which consisted of (40) paragraphs, and the apparent validity of the research tool was verified by presenting it to experts and specialists in educational and psychological sciences. The discriminatory power of the tool was also calculated, as the number of paragraphs of the scale in its final form reached (40) paragraphs, and the reliability was calculated in two ways: retesting; as the value of the Pearson correlation coefficient reached (0.86) and the Cronbach’s alpha method; as the value of the reliability coefficient reached (0.84(. After statistically analyzing the data in the statistical package program (SPSS), the researcher reached the following results: Mosul University students have an above-average level of psychological boredom, and no significant differences appeared between the average psychological boredom of the individuals in the research sample according to the gender variable, while there were significant differences between the average psychological boredom achieved among individuals during the research according to the specialization variable in favor of the scientific, while there was a significant difference between the average psychological boredom achieved among students in the academic year (second - fourth) in favor of the fourth grade. Based on the results reached by the researcher recommended that psychological counselling centers should provide student services at universities for the necessary psychological support for students to reduce the severity of anxiety and psychological boredom and improve the quality of life. The researcher proposed several proposals, including conducting research to identify the correlation between psychological boredom and other psychological variables that were not addressed by the current research (personality type - emotional stability).